## 2 (x + 1) = 6x – 46

### x = 12

To solve for x in the equation 2(x+1)=6x-46, you can start by distributing the 2 on the left side of the equation:

2x + 2 = 6x – 46

Next, you can isolate x on one side of the equation and the constants on the other side. To do this, you can subtract 2x from both sides:

2 = 4x – 46

Adding 46 to both sides:

48 = 4x

Dividing both sides by 4:

x = 12

Therefore, the solution for the equation 2(x+1)=6x-46 is x = 12.

##### More Answers:

The Less Than Comparison Operator In Math And Programming.Master The Art Of Communication: Boost Your Vocabulary With Opposites

Negative Numbers: A Crucial Tool For Solving Complex Mathematical Problems

Error 403 The request cannot be completed because you have exceeded your quota. : quotaExceeded